Primary health care as the main guarantor of a healthy population in the country and a global challenge in the world: a systematic review [version 2; peer review: 1 approved, 2 approved with reservations, 1 not approved] - Gulnara Abashidze-Gabaidze; Lasha Loria; Lali Khurtsia; Mishiko Gabaidze (F1000Research)
Background Primary health care (PHC) is a fundamental aspect of healthcare systems globally, playing a crucial role in maintaining the health of the population. Despite its importance, there are still gaps in the delivery of PHC services. This study aims to analyze the healthcare system and the existing gaps to develop strategies for improving PHC services. Methods This study is a mixed method a combination of documentary analysis and narrative synthesis as an alternative to meta-analysis. For our systematic review, we primarily focused on articles published within the last 10 years. However, we also included some older articles (published between 2003 and 2009) that provided valuable insights into the historical context and evolution of primary healthcare systems. Data of each article reviewed during the review - Study, Article, Study setting, Study design, Study assessment, Study suggestions are presented in Table 1. A total of 38 articles were reviewed. The data sources include peer-reviewed articles and other relevant literature on PHC services. With appropriate keywords. Results The study identifies gaps in PHC services, including issues with access to care, affordability, and quality of care. It provides insights into the challenges faced by PHC systems worldwide, highlighting the need for strategies to address these issues. Conclusions The study contributes to a better understanding of the challenges faced by PHC systems worldwide and provides insights for policymakers and healthcare providers to improve healthcare services. The systematic review, which focuses on PHC, was conducted following the PRISMA guidelines. The PRISMA diagram of study selection was used to illustrate the process of article inclusion and exclusion. Table 1 provides a summary of the key information from the selected articles.